Sistem Informasi Kenaikan Pangkat Karyawan Pada Dinas Pekerjaan Umum (PU) Dan Energi Sumber Daya Mineral (ESDM) Kabupaten Lombok Tengah - Mahni Pitriyawati; Khairul Imtihan (LPPM STMIK Lombok, 2018)
Along with the increasingly tight competition of technology and information, making many government parties in Indonesia use technology as a supporter to improve its performance. The development of information technology systems led to changes in the role of information technology systems ranging from the role of efficiency, effectiveness to the strategic role, the existence of computerized data processing information becomes very important. That's because computerized data processing can contribute greatly to a company's performance, when compared to manual data processing. (Imtihan, 2015) Dinas Pekerjaan Umum (PU) dan Energi Sumber Daya Mineral (ESDM) Kota Praya Kabupaten Lombok Tengah do not have a computerized system for data processing promotion of employees, still done manually and data storage is still archive so as to enable the loss of damaged data or archive and also takes longer time in data processing employees. The process can create a continuous error and since the promotion is routinely given to the employee, it is necessary to create an information system that can manage the promotion process automatically in order to avoid mistakes or continuous errors such as errors when data lost or damaged archives and accelerate in time processing data employee who will conduct the promotion process so that required a computerized promotion information system that can regulate the process of promotion of employees. The information system is built using PHP programming language and Mysql database. Data collection method used in this research is the method of observation, interview, and literature study. The method of analysis used is SWOT method, design method used in this research is waterfall method and testing method used is black box testing method. The result of this research is to produce information system of processing process of promotion of employee to facilitate the employee in search process of promotion data and can facilitate officer at the time of data processing increase of employee pangat and also to minimize mistake of data processing promotion of employee rank.